2021
DOI: 10.3390/ani11123473
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Alternatives to Locomotion Scoring for Lameness Detection in Pasture-Based Dairy Cows in New Zealand: Infra-Red Thermography

Abstract: Lameness in cattle is a complex condition with huge impacts on welfare, and its detection is challenging for the dairy industry. The present study aimed to evaluate the association between foot skin temperature (FST) measured using infrared thermography (IRT) and locomotion scoring (LS) in dairy cattle kept at pasture. Data were collected from a 940-cow dairy farm in New Zealand. Cows were observed at two consecutive afternoon milkings where LS was undertaken at the first milking (4-point scale (0–3), DairyNZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 58 publications
3
17
6
Order By: Relevance
“…The speci city and sensitivity of IRT at our 38.0 cut-off point for identifying cows with a locomotion score of ≥ 2 were both moderate (86.0 and 73.2%, respectively) and lower than the speci city and sensitivity we reported in New Zealand of 92.4 and 80.0%, respectively (Werema et al, 2021). However, as with the difference between the two studies in relation to optimal cut-off, the difference between our two studies is much less than the differences between previous studies, which have reported the speci city and sensitivity of IRT.…”
Section: Thermography As a Predictor Of Locomotion Scorecontrasting
confidence: 78%
See 4 more Smart Citations
“…The speci city and sensitivity of IRT at our 38.0 cut-off point for identifying cows with a locomotion score of ≥ 2 were both moderate (86.0 and 73.2%, respectively) and lower than the speci city and sensitivity we reported in New Zealand of 92.4 and 80.0%, respectively (Werema et al, 2021). However, as with the difference between the two studies in relation to optimal cut-off, the difference between our two studies is much less than the differences between previous studies, which have reported the speci city and sensitivity of IRT.…”
Section: Thermography As a Predictor Of Locomotion Scorecontrasting
confidence: 78%
“…Additionally, the order was consistent across claws, such as if on the lateral claw, zone 1 had a higher mean temperature than zone 2, the same applied to zones 5 and 6 on the medial claw. However, the order was not the same as that reported by Werema et al (2021). In the current study, zones 1 and 5 (coronary band) had a higher mean temperature than zones 3 and 7 (below accessory digit), whereas Werema et al (2021) reported that zones 3 and 7 had a higher temperature than zones 1 and 5.…”
Section: Effect Of Claw and Zone On Foot Temperaturecontrasting
confidence: 75%
See 3 more Smart Citations